Reproduction, race, and gender in philosophy and the early life sciences - Lettow, Susanne (SUNY series, philosophy and race, 2014)
"Investigates the impact of theories of reproduction and heredity on the emerging concepts of race and gender at the end of the eighteenth and the beginning of the nineteenth centuries"--Provided by publisher.